Microablative Erbium: YAG Laser Therapy for Vulvodynia – A Report on Efficacy, Safety, and Treatment Satisfaction. Issue 6 (19th September 2021) - Trutnovsky, Gerda; Bliem, Brigitte; Greimel, Elfriede; Tamussino, Karl; Gold, Daniela
Abstract: Introduction: Treatment for vulvodynia is challenging and a multidisciplinary approach is recommended. Aim: To examine the effectiveness, safety and treatment satisfaction of vulvovaginal microablative laser treatment for vulvodynia. Methods: Case study of women who received laser treatment as part of a multidisciplinary treatment program for vulvodynia. Subjective improvement was compared to a retrospective cohort of women treated for vulvodynia without LASER therapy. LASER treatment was offered to women with vulvodynia presenting to a gynecologic pain clinic of a tertiary university hospital. LASER treatments were performed with a microablative 2, 940 nm Er:YAG LASER and potentially repeated after 1 month. Main outcome measures: Change in local vulvar pain was assessed with cotton-swab tests and rated on a numeric rating scale (NRS). Treatment discomfort and short-term adverse events were recorded. The Freiburg Index of Patient Satisfaction was used to assess treatment satisfaction. Subjective symptom improvement was assessed with the Patient Global Impression of Improvement questionnaire. Results: 35 women received at least 1 laser treatment, with overall mild treatment adverse effects (mean pain NRS 2.4 ± 1.9) and good treatment satisfaction (mean total score of 27.6 ± 5.1; potential range 8–32). One month after last LASER treatment the pain NRS on vulvar cotton swab test improved from 6.1 ± 2.6 at baseline to 3.1 ± 2.6 ( P < .001), and 74% of women (n = 26) reported symptom improvement. At 9–12 months follow-up 66% reported ongoing symptom improvement, with no significant difference to the control group of 32 women. Conclusion: Microablative Er:YAG vulvovaginal LASER therapy appears safe and well accepted among vulvodynia patients, but there was no significant difference in symptom improvement compared to a control group.